Infection Rate of Trypanosoma cruzi (Trypanosomatida: Trypanosomatidae) in Dipetalogaster maxima (Hemiptera: Reduviidae). Issue 1 (27th August 2021) - Flores-López, Carlos Alberto; Rivas-García, Lynneth; Romero-Figueroa, Guillermo; Guevara-Carrizales, Aldo; Peiro-Nuño, Haran; López-Ordoñez, Teresa; Bello-Bedoy, Rafael
Abstract: Chagas disease is caused by the infection of the parasite Trypanosoma cruzi (Chagas, 1909). Mexico is estimated to be among the countries with the highest rates of human infections. The southernmost region of the Baja California peninsula is home to the endemic, highly aggressive, and largest Triatominae vector, thus far described: Dipetalogaster maxima (Uhler 1894 ). Previous single-year studies have attempted to estimate the natural infection rate of T. cruzi in this species, none encompassing a multiyear sampling design nor a species-specific diagnostic tool. We report the infection rate based on more than 717 individuals examined via a PCR species-specific diagnosis. The infection rate of T. cruzi was of 4.4% ( n = 5/112), 0.9% ( n = 4/411), and 4.6% ( n = 9/194) for 2016, 2017, and 2018, respectively, resulting in an infection rate of 2% across all sites and years ( n = 18/717). Graphical Abstract: